Changes in Anti-SARS-CoV-2 IgG Subclasses over Time and in Association with Disease Severity - Zoia R. Korobova; Elena V. Zueva; Natalia A. Arsentieva; Oleg K. Batsunov; Natalia E. Liubimova; Irina V. Khamitova; Raisa N. Kuznetsova; Artem A. Rubinstein; Tikhon V. Savin; Oksana V. Stanevich; Alexandr N. Kulikov; Dmitry E. Pevtsov; et al. (Viruses, 2022)
IgG is the most prominent marker of post-COVID-19 immunity. Not only does this subtype mark the late stages of infection, but it also stays in the body for a timespan of at least 6 months. However, different IgG subclasses have different properties, and their roles in specific anti-COVID-19 responses have yet to be determined. We assessed the concentrations of IgG1, IgG2, IgG3, and IgG4 against different SARS-CoV-2 antigens (N protein, S protein RBD) using a specifically designed method and samples from 348 COVID-19 patients. We noted a statistically significant association between severity of COVID-19 infection and IgG concentrations (both total and subclasses). When assessing anti-N protein and anti-RBD IgG subclasses, we noted the importance of IgG3 as a subclass. Since it is often associated with early antiviral response, we presumed that the IgG3 subclass is the first high-affinity IgG antibody to be produced during COVID-19 infection.